2015
DOI: 10.1118/1.4921366
|View full text |Cite
|
Sign up to set email alerts
|

Multiatlas whole heart segmentation of CT data using conditional entropy for atlas ranking and selection

Abstract: The authors have developed a new MAS framework for automatic WHS of CTA and investigated alternative implementations of MAS. With the proposed atlas ranking algorithm and joint label fusion, the MAS scheme is able to generate accurate segmentation within practically acceptable computation time. This method can be useful for the development of new clinical applications of cardiac CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 44 publications
(79 reference statements)
4
48
0
Order By: Relevance
“…The inconsistency between results for coronary CTA and CT PET is also clearly demonstrated by the Box-and-Whisker plots in Figure 4. Compared to the segmentation results from Kirisli et al 27 and Zhuang et al, 30 the results in this article are satisfactory.…”
Section: Resultssupporting
confidence: 51%
“…The inconsistency between results for coronary CTA and CT PET is also clearly demonstrated by the Box-and-Whisker plots in Figure 4. Compared to the segmentation results from Kirisli et al 27 and Zhuang et al, 30 the results in this article are satisfactory.…”
Section: Resultssupporting
confidence: 51%
“…In our study, all images had slice spacing of 2.5 mm, which may limit distance-based assessment. By considering the limitation of image resolution, our auto-segmentation approach is comparable to state-of-the-art cardiac segmentation methods [2931], which were applied to contrast CT images with sub-millimeter resolution for diagnosis of cardiovascular diseases. On the other hand, this showed that the atlases we developed are useful for auto-contouring the cardiac substructures.…”
Section: Discussionmentioning
confidence: 99%
“…With both approaches, considerable research effort has been directed toward the construction of brain atlases . A variety of methods have been also proposed for the segmentation of other organs or anatomical structures by means of atlases . However, the number of studies related to the construction of spinal atlases is limited and some of them are centred on structures like the intervertebral discs or the spinal canal .…”
Section: Introductionmentioning
confidence: 99%
“…35 A variety of methods have been also proposed for the segmentation of other organs or anatomical structures by means of atlases. [36][37][38][39][40][41][42] However, the number of studies related to the construction of spinal atlases is limited and some of them are centred on structures like the intervertebral discs 43 or the spinal canal. 44,45 Regarding vertebrae, Hardisty et al 46 presented an algorithm to perform the segmentation of tumorinvolved vertebrae using demons deformable image registration and level set methods.…”
Section: Introductionmentioning
confidence: 99%